In-silico identification and characterization of O-methyltransferase gene family in peanut (Arachis hypogaea L.) reveals their putative roles in development and stress tolerance - Cai, Tiecheng; Sharif, Yasir; Zhuang, Yuhui; Yang, Qiang; Chen, Xiangyu; Chen, Kun; Chen, Yuting; Gao, Meijia; Dang, Hao; Pan, Yijing; Raza, Ali; Zhang, Chong; et al. (Frontiers in Plant Science, 2023)
Cultivated peanut (Arachis hypogaea) is a leading protein and oil-providing crop and food source in many countries. At the same time, it is affected by a number of biotic and abiotic stresses. O-methyltransferases (OMTs) play important roles in secondary metabolism, biotic and abiotic stress tolerance. However, the OMT genes have not been comprehensively analyzed in peanut. In this study, we performed a genome-wide investigation of A. hypogaea OMT genes (AhOMTs). Gene structure, motifs distribution, phylogenetic history, genome collinearity and duplication of AhOMTs were studied in detail. Promoter cis-elements, protein-protein interactions, and micro-RNAs targeting AhOMTs were also predicted. We also comprehensively studied their expression in different tissues and under different stresses. We identified 116 OMT genes in the genome of cultivated peanut. Phylogenetically, AhOMTs were divided into three groups. Tandem and segmental duplication events played a role in the evolution of AhOMTs, and purifying selection pressure drove the duplication process. AhOMT promoters were enriched in several key cis-elements involved in growth and development, hormones, light, and defense-related activities. Micro-RNAs from 12 different families targeted 35 AhOMTs. GO enrichment analysis indicated that AhOMTs are highly enriched in transferase and catalytic activities, cellular metabolic and biosynthesis processes. Transcriptome datasets revealed that AhOMTs possessed varying expression levels in different tissues and under hormones, water, and temperature stress. Expression profiling based on qRT-PCR results also supported the transcriptome results. This study provides the theoretical basis for further work on the biological roles of AhOMT genes for developmental and stress responses.